Recent Advances in Antimicrobial Coatings and Material Modification Strategies for Preventing Urinary Catheter-Associated Complications - S. P. Yamini Kanti; Ildikó Csóka; Orsolya Jójárt-Laczkovich; Lívia Adalbert (Biomedicines, 2022)
In recent years, we have witnessed prominent improvements in urinary catheter coatings to tackle the commonly occurring catheter-associated urinary tract infection (CAUTI) in catheterized patients. CAUTIs are claimed to be one of the most frequent nosocomial infections that can lead to various complications, from catheter encrustation to severe septicaemia and pyelonephritis. Besides general prevention hygienic strategies, antimicrobial-coated urinary catheters show great potential in the prevention of urinary catheter-associated complications. The aim of this review is to present and evaluate recent updates on the development of antimicrobial urinary catheters in the context of the aetiology of urinary malfunction. Subsequently, we shed some light on future perspectives of utilizing 3D printing and the surrounding regulatory directions.